PENINGKATAN PEMAHAMAN SISWA MA AL ADZKAR MRANGGEN DEMAK MENGENAI PERLINDUNGAN HUKUM BAGI REMAJA PEREMPUAN - surayda, helen intania (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2020)
The embodiment of the mandate for the protection of human rights (human rights) as the constitutional rights of citizens that strengthen human rights has also been carried out through a number of Laws, including the ratification of a number of international human rights instruments so as to become national law. Cases against women are one form of human rights violations experienced by men. The vast majority of cases of violence experienced are sexual violence that occurs as a result of social construction placing certain gender relationship positions more dominant in society against others resulting in actions that result in physical, mental, and sexual harm, including threats, coercion, and deprivation of liberty. Women in subordinate relationship positions versus dominant males are often stereotyped, as well as acts of violence with a form of control even with the intent of protection, which eliminates physical and mental integrity resulting in loss of persaman, connoisseur and basic freedom as a human being. The core legal protection against women victims of sexual violence in DUHAM respects everyone's humanity because she was born a human being. Courtship violence is part of violence against women. Cases of domestic violence not only afflict adult women but can unwittingly also afflict teenagers who are in courtship, so based on this can be formulated the problem in this Community Service activity is the lack of understanding ma Al-Adzkar Mranggen, Demak on "Legal Protection for YoungWomen". This   Community Service activity is conducted by method of   lectures,   discussions and q&A. In this Community Service activity, MA Al Adzkar students gained information and understanding about the legal   protection of   young   women. The results of this activity showed that,   siswi prior to the implementation of the activity, MA Al   Adzkar students did not understand and understand, and after the counseling of MA Al   Adzkar students increased the insight into the legal needs for young   women,this was shown by an increase in the average generalunderstanding of 15   participants by 77.33%.